Analisis Pengaruh Kemampuan Berinovasi, Keterlibatan Pelanggan, dan Adopsi Media Sosial terhadap Kinerja Inovasi UMKM - Alfian Prasetya; Anjar Priyono (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
MSMEs support most of Indonesia's economic portion. To improve MSMEs performance, it is necessary to develop innovation capabilities, customer engagement, and social media adoption in business. Therefore, this study aims to determine whether innovation capabilities, customer engagement, and social media adoption can improve MSMEs innovation performance which is expected to improve overall MSMEs performance. This quantitative study distributed questionnaires to 100 respondents domiciled in Sleman Regency, Yogyakarta. Then, the data were processed using structural equation modeling techniques (SEM) with SmartPLS software. The results show that innovation capabilities have a directly significant effect on MSMEs innovation performance, but are not proven to significantly moderate the effect of social media adoption on MSMEs innovation performance. Social media adoption is proven to have a significantly positive effect on MSMEs innovation performance. Customer engagement is not proven to have a significant effect on MSMEs innovation performance, either directly or in moderating the effect of social media adoption. This study also shows that there are other variables that can affect MSMEs innovation performance apart from innovation capabilities, customer engagement, and social media adoption.